Anxiety in children: let’s overcome it together - Mokrii Мар’яна; Frankova Ірина (Psychosomatic Medicine and General Practice, 2018)
Can you imagine how it would feel when everything inside you is telling you something is wrong, but the person you trust keeps telling you there’s nothing to worry about? This article disclose important information regarding anxiety in children and how to overcome it.